The Effect of Single-Dose Massage Session on Autonomic Activity, Mood, and Affective Responses in Major Depressive Disorder. (December 2019) - Hohl, Rodrigo; Deslandes, Andréa Camaz; Mármora, Cláudia Helena Cerqueira
Background: Massage therapy (MT) is a holistic procedure that includes hand pressure (HP), therapeutic communication (TC), and attentive care (AC); together, these procedures could decrease symptoms of depression.Purpose: To study the influence of TC and AC during MT.Methods: Within-subject experimental design with counterbalancing order of treatment. Comparison analysis of the effect of a typical Swedish massage session (SM) with a "sham" massage (ShM; without HP) on the heart rate variability (HRV) mood and affective responses of patients with major depressive disorder ( N = 11). During the ShM, clay stones were randomly placed on the body, and the patients were informed about the (sham) therapeutic effect of stones.Findings: A main effect of time showed that after intervention, both SM and ShM increased the HRV (high-frequency power; F [1, 10] = 7.58, p = .02) and reduced scores for anxiety ( F [1, 10] = 37.57, p < .001), other feelings ( F [1, 10] = 22.64, p = .001), and physical sedation ( F [1, 10] = 10.72, p = .008). The SM was associated with more positive affective responses than ShM (qualitative analysis).Conclusions: AC and TC included in MT session improved mood and HRV in the absence of HP. Additional effect on affective responses was observed owing to the HP.